Paraphenylenediamine Poisoning and Recovery from Acute Renal Failure Subsequent to Haemodialysis - Ashok Kumar Lohano, Akber Hussain Yousfani, Aftab Ahmed Malik, Sharnsuddin Shaik (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To determine the frequency of nephrotoxicity and recovery from Acute renal failure subsequent to Haemo dialysis in patients with diaphenylpararnine poisoning Methods: Our study is a transversal study, accomplished in Peoples Medical College Hospital. Nawabshah. Medical wards & Intensive care unit (ICU) were surveyed for a period of 6 months. 99 patients with Para-phenylenediamine poisoning duration of ingestion or exposure more than 12 hours having acute renal failure were selected with early Haemodialysis. Results: It revealedOut of 99 patients, there are 40 male cases and 59 are females. The average age of the patients was34 5yrs. A high recovery rate is also observed in both the genders following Haemodialysis .The death rate was 29% . Conclusion: Early management and early Haemo dialysis in acute kidney failure can decrease the mortality associated with PPD poisoning.. A greater importance should be given to spot the locale of use of hair dyes containing PPD so as to control and overcome serious complications related to PPD poisoning in OUT social order.